The terror - Corman, Roger, 1926-; Gordon, Leo V., 1922-2000; Hill, Jack, 1933 January 28-; Karloff, Boris, 1887-1969; Filmgroup (1959-1962) (United States : American-International Pictures : Filmgroup Production, 1963)
The macabre story of a man, "The Baron", who, on his return from war, finds his wife in the arms of another man. He kills them and remorsefully buries his wife in the castle. A French soldier lost in the region asks for shelter in the old castle, but at night the ghost of the murdered woman appears.--
Boris Karloff, Jack Nicholson, Sandra Knight, Richard Miller, Dorothy Neumann, Jonathan Haze.
Director of photography, John Nicholaus ; film editor, Stuart O'Brien ; music, Ronal Stein.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: Motion pictures; Horror films; Feature films; Streaming video